2002
DOI: 10.4049/jimmunol.168.3.1244
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-19 Is Expressed in Myeloid Cells in an Adhesion-Dependent Manner and Associates with the Cell Surface

Abstract: We have previously reported the isolation of the human matrix metalloproteinase (MMP)-19 (also referred to as RASI) from a synovium of a patient suffering from rheumatoid arthritis and its expression at the cell surface of activated PBMC. In this study, we have analyzed the regulation and cell surface expression of human MMP-19 in several human cell lines and blood-derived cells. Among the cell lines analyzed, MMP-19 is largely expressed by lung fibroblasts as well as by myeloid cell lines THP-1 and HL-60. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 32 publications
5
32
0
Order By: Relevance
“…Both matrix metalloproteinases (15 and 19) were expressed by stromal fibroblasts in high percentage and by macrophages in smaller amounts, which is in accordance with previous data on cell types expressing MMP-19 (28,29). Several studies using mouse models of genetically altered fibroblasts demonstrated a direct involvement of resident fibroblasts in the onset of cancer (30); moreover, both genetic and cell-biology studies indicate that tumor growth is not just determined by malignant cancer cells themselves, but also by the tumor stroma (31).…”
Section: Discussionsupporting
confidence: 81%
“…Both matrix metalloproteinases (15 and 19) were expressed by stromal fibroblasts in high percentage and by macrophages in smaller amounts, which is in accordance with previous data on cell types expressing MMP-19 (28,29). Several studies using mouse models of genetically altered fibroblasts demonstrated a direct involvement of resident fibroblasts in the onset of cancer (30); moreover, both genetic and cell-biology studies indicate that tumor growth is not just determined by malignant cancer cells themselves, but also by the tumor stroma (31).…”
Section: Discussionsupporting
confidence: 81%
“…In tissue samples, TNF-␣ protein was expressed in the keratinocytes adjacent to MMP-19-positive cells. The fact that TNF-␣ induces adhesion molecules and that it stimulates MMP-19 could also suggest that MMP-19 is a reconstructive enzyme in the repair of destroyed BM and that cell adhesion might have an effect on its expression, as shown in myeloid cells 40 or by comparing to the presence of E-cadherin. However, caution is needed when extrapolating results from cell culture to tissue in vivo since, based on transgenic mouse studies, many cytokines have different effects on keratinocytes in vivo and in culture.…”
Section: Northern and Western Analyses Of Keratinocytesmentioning
confidence: 99%
“…In this respect, consistent evidences highlight a role in the modulation of cell motility even under physiological conditions: degradation of laminin is associated to promotion of epithelial cells as well as keratinocytes migration and proliferation (Sadowski et al, 2003(Sadowski et al, , 2005. Myeloid cells and T-lymphocytes efficiently compartmentalize the enzyme at their leading edge through interaction with unknown cell surface molecules, to improving extravasation and migration toward the flogistic site (Beck et al, 2008;Mauch et al, 2002). Additional evidence of a positive influence of MMP-19 in tumor growth come from studies in vitro on breast cancer cells where siRNA-mediated inhibition of the enzyme down-regulates tumor invasiveness (Hegedüs et al, 2008).…”
Section: Biological Featuresmentioning
confidence: 99%